The role of ownership map in constraining discretionary loan loss-provisions decisions in Jordanian banks - Alaa Mohammad AlQudah; Mohammad Jamal Azzam; Ayman Ahmad Abu Haija; Ayman Ahmad Abu Haija; Safaa Adnan AlSmadi (Cogent Business & Management, 2020)
Banks' shareholders are mainly concerned with maximizing their profits. As a result of passing their monitoring tasks to another group (managers), the maximization goal could be threatened by manipulating bank's provisions to accomplish a specific set of goals for managers. Hence, introducing active owners in banks ownership map is expected to reduce the agency problem among the different groups inside the bank. In line with this argument, this study aims mainly to explore the monitoring ability of different types of owners within the Jordanian banks listed on the Amman Stock Exchange in reducing the adoption of loan loss provisions (LLP) techniques to manipulate earnings figures. Selecting fifteen listed banks between 2013 and 2018, and applying a multivariate analysis, guide to the main findings of the study which introduced foreign owners, institutional owners, and blockholders owners as deterrent players in accepting LLP manipulations. However, family and managerial ownership showed a low level of conservatism in reducing LLP techniques within the Jordanian banking sector. The findings of this study present several shares of evidences that the ownership map in Jordanian banks needs more efforts and experience to protect bank's earnings from being expropriated by banks boards members. Interestingly, this study adds to the current literature by exploring the roles of the various types of owners in constraining LLP techniques from a developing market such as Jordan.
Keywords: 650; loan-loss provisions; ownership structure; Jordan and banks